Simultaneous adsorption of heavy metals from aqueous matrices by nanocomposites: A first systematic review of the evidence - Seyyed Abbas Mirzaee; Neemat Jaafarzadeh; Susana Silva Martinez; Zahra Noorimotlagh (Environmental Health Engineering and Management, 2022)
Background: Nanocomposites have received remarkable attention as effective adsorbents for removal of coexisting pollutants over the last decades. The presence of heavy metals (HMs) in wastewater has caused a global health concern. Therefore, the aim of this study was to review the most relevant publications reporting the use of nanostructures to simultaneous adsorption of HMs in mixed aqueous systems. Methods: In this systematic review, 9 studies were included through a systematic search in the three databases (ISI, Scopus, and PubMed) during 1990-2021. The optimal value of simultaneous adsorption parameters such as initial concentration, contact time, adsorbent dosage, and pH was discussed. Results: Findings indicate that the Langmuir and Freundlich models and the pseudo-second-order kinetic model have been widely used and the most popular models to describe the equilibrium of HMs by nanoadsorbents. This study confirmed that the simultaneous removal rate of HMs decreased with an increase in pH value. It was found that the major mechanisms of HMs adsorption onto nanostructures were electrostatic interactions and precipitation. Conclusion: Nanocomposites have remarkable adsorption performance for HMs with the highest adsorption capacity (qe(mg/g)).